All the blood we share eaudiobook A novel of the bloody benders of kansas. - Bruce, Camilla (Penguin Audio, 2022)
A sinister novel based on the real Bloody Benders, a family of serial killers in the old West bound by butchery and obscured by the shadows of American history. The winds shift nervously on the Kansas plain whispering of travelers lost and buried, whispering of witches. Something dark and twisted has taken root at the Bender Inn. At first the townspeople of Cherryvale welcome the rising medium Kate Bender and her family. Kate's messages from the Beyond give their tedious dreams hope and her mother's potions cure their little ills—for a price. No one knows about their other business, the shortcut to a better life. And why shouldn’t their family prosper? They’re careful. It’s only from those who are marked, those who travel alone and can easily disappear, that the Benders demand their pound of flesh.   But even a gifted seer like Kate can make a misstep. Now as the secrets festering beneath the soil of the family orchard threaten to bring them all to ruin, the Benders must sharpen their craft—or vanish themselves.